Complete 1H and 13C NMR chemical shift assignments of mono-to tetrasaccharides as basis for NMR chemical shift predictions of oligo- and polysaccharides using the computer program CASPER. (March 2022) - Furevi, Axel; Ruda, Alessandro; Angles d'Ortoli, Thibault; Mobarak, Hani; Ståhle, Jonas; Hamark, Christoffer; Fontana, Carolina; Engström, Olof; Apostolica, Patricia; Widmalm, Göran
Abstract: Carbohydrate structure can be elucidated or confirmed by using NMR spectroscopy as the prime technique. Prediction of 1 H and 13 C NMR chemical shifts by computational approaches makes this assignment process more efficient and the program CASPER can perform this task rapidly. It does so by relying on chemical shift data of mono-, di-, and trisaccharides. In order to improve accuracy and quality of these predictions we have assigned 1 H and 13 C NMR chemical shifts of 30 monosaccharides, 17 disaccharides, 10 trisaccharides and one tetrasaccharide; in total 58 compounds. Due to different rotamers, ring forms, α- and β-anomeric forms and pD conditions this resulted in 74 1 H and 13 C NMR chemical shift data sets, all of which were refined using total line-shape analysis for the 1 H resonances in order to obtain accurate chemical shifts. Subsequent NMR chemical shift predictions for three sialic acid-containing oligosaccharides, viz., GD1a, a disialyl-LNnT hexasaccharide and a polysialic acid-lactose decasaccharide, and NMR-based structural elucidations of two O-antigen polysaccharides from E. coli O174 were performed by the CASPER program (http://www.casper.organ.su.se/casper/ ) resulting in very good to excellent agreement between experimental and predicted data thereby demonstrating its utility for carbohydrate compounds that have been chemically or enzymatically synthesized, structurally modified or isolated from nature. Graphical abstract: Image 1 Highlights: NMR chemical shift data were obtained for mono- to tetrasaccharides. 1 H resonances were refined by total line-shape analysis. Chemical shift predictions were made for sialic acid-containing oligosaccharides. NMR-based structural elucidations were carried out for E. coli O174 O-antigens.